Continuing professional development a practical approach : managing your CPD as a professional engineer - Lorriman, John (London, United Kingdom Institution of Engineering and Technology, 1997)
This book came about as a result of many years of personal commitment to continuing professional development. A key message in this book is that each one of us needs to take personal responsibility for our own competence and career development - and to a very high degree, as well as continually. Another message is that organisations need to redefine the role of managers in a fundamental way if CPD is to be successful. Thirdly, the providers of CPD need to rethink their approach, so that the learners are best able to relate their learning to specific competence and career development objectives. Fourthly, the professional institutions need to do as much as possible to learn from each other's successes and good ideas.
Electronic reproduction.
Keywords: Career development; Engineers; Professional education; Electronic books